Comprehensive comparison of SOFCs with proton-conducting electrolyte and oxygen ion-conducting electrolyte: Thermoeconomic analysis and multi-objective optimization. (1st February 2020) - Mojaver, Parisa; Chitsaz, Ata; Sadeghi, Mohsen; Khalilarya, Shahram
Highlights: A comparative analysis was conducted on performance of SOFC-O 2− and SOFC-H + . Energy, exergy, economic, and environmental analyses were performed. Multi-objective optimization procedure using evolutionary algorithm was conducted. SOFC-O 2− had a better performance compared to SOFC-H + in almost all cases. System based SOFC-O 2− had a higher exergy efficiency and lower SUCP. Abstract: A power generation system based on integrated methane fed solid oxide fuel cell (SOFC) and organic Rankin cycle (ORC) was modeled and validated against experimental results available in the literature. A comprehensive comparative analysis was conducted on the system performance based the oxygen ion-conducting electrolyte SOFC (SOFC-O 2− ) and proton-conducting electrolyte SOFC (SOFC-H + ) electrolyte. The comparative analysis was conducted from viewpoints of energy, exergy, economic, and environmental. Current density and stack temperature were considered as the input variables. The multi-objective optimization procedure based on an evolutionary algorithm was conducted in the presence of exergy efficiency and sum of the unit cost of the products (SUCP) as the objective functions. The performance of the SOFC-O 2− and the SOFC-H + based power generation systems were compared at their optimum conditions. The system based the SOFC-O 2− had a better performance compared to the system based the SOFC-H + from the objective functions viewpoints. The system based the SOFC-O 2− had a higher exergy efficiency (60.20% compared to 54.06%) and lower SUCP (48.24 /GJ compared to 48.75 /GJ) than the system based the SOFC-H + at their optimum conditions. The SOFC-O 2− produced 18 kW power higher than the SOFC-H + . This led to increase the system power from 147.9 kW in the case of the SOFC-H + to 156.4 kW for the SOFC-O 2− .